The integrated design of building services by an equipped and eco-efficient module (MOTE2) - Roberto Giordano; Cristina Allione; Andrè Clos; Elena Montacchini; Silvia Tedesco (Vitruvio: International Journal of Architectural Technology and Sustainability)
The targets set out by European Directives concerning the energy savings in the construction sector refer both to building envelope and to its services. With regard to building services it is mandatory meeting requirements related to heating, cooling, lighting and ventilation.